Aircraft engine design - Mattingly, Jack D.; Boyer, Keith M.; Haven, Brenda A.; Heiser, William H.; Pratt, David T. (Reston, Virginia : American Institute of Aeronautics and Astronautics, Inc., 2018)
"Aircraft Engine Design, Third Edition presents a complete and realistic aircraft engine design experience. From the request for proposal for a new aircraft to the final engine layout, it outlines the concepts and procedures required for the entire process. The writing of the third edition of Aircraft Engine Design began as soon as the second edition was published in 2003. The ensuing 15 years of evolutionary changes have created an improved, new work. The special contributions of uniquely quali?ed experts continue to provide valuable material to this new edition. These include Appendix L on Turbine Engine Life Management by Dr. William D. Cowie and Appendix M on Engine Controls by Charles A. Skira (with Timothy J. Lewis and Zane D. Gastineau) with update by Dr. Link Jaw"--
Includes bibliographical references and index.
Keywords: Aircraft gas-turbines -- Design and construction